ROLE OF ACCESS OSTEOTOMY IN HEAD AND NECK LESIONS – A REVIEW - K, BHARATHI; CHANDRASEKAR, MANOJ; KUMAR S, KAPIL DEV; GUPTA B, BALA JAGANNATH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
The surgical resection of the head and neck lesions summarizes the principles, classifications, applications, complications, and post-operative care of osteotomy with the standard protocols performed safely. It often poses a great surgical challenge due to the anatomical complexity, difficulty in accessibility, and proximity of vital structures. A multidisciplinary approach is often required in these situations for their better exposure to provide surgical access. Access osteotomy is the choice and type for these head and neck lesions, which are most often based on the anatomic extent of the lesion, vascularity of the lesion, and involvement of neurovascular structures in and around it. The literature search using Medline from the year 1986 to 2019 were performed and textbooks were also collected by hand search from the same period. The role of aggressive surgical resection has not been established for malignant head and neck lesions with the technical feasibility and its efficacy for specific tumor types must be defined by the future studies. Thus, we would like to conclude that access osteotomy allows the surgeon a better view and an access of the surgical field to resect the tumor completely with safer margins, preserving the vital structures, pre-operative functions, and reducing post-operative complications.